Enhanced Performance of Perovskite Single-Crystal Photodiodes by Epitaxial Hole Blocking Layer - Pan, Yuzhu; Wang, Xin; Xu, Yubing; Li, Yuwei; Elemike, Elias Emeka; Shuja, Ahmed; Li, Qing; Zhang, Xiaobing; Chen, Jing; Zhao, Zhiwei; Lei, Wei (Frontiers in Chemistry, 2020)
Introducing hole/electron transporting and blocking layers has been considered to enhance the performance of electronic devices based on organic–inorganic hybrid halide perovskite single crystals (PSC). In many photodiodes, hole/electron transporting or blocking materials were spin-coated or thermal-evaporated on PSC to fabricate heterojunction. However, the heterojunction interfaces due to lattice mismatching between hole/electron transporting or blocking materials and perovskites easily form traps and cracks, which cause noise and leakage current. Besides, these low mobility transporting layers increase the difficulty of transporting carries generated by photons to the electrode, so it also increases the responding time for the photo detection. Herein, an MAPbCl3–MAPbBr2.5Cl0.5 heterojunction interface was realized by liquid phases epitaxy, in which MAPbBr2.5Cl0.5 PSC acts as active layer and MAPbCl3 PSC as hole blocking layer (HBL). Our PIN photodiodes with epitaxial MAPbCl3 PSC as HBL show better performance in dark current, light responsivity, stability and response time than the photodiodes with spin-coated organic PCBM as HBL. These results suggest that the heterojunction interface formed between two bulk PSCs with different halide compositions by epitaxy growth is very useful for effective blocking injected charges under high external electric field, which could improve the collection of photo-generated carriers so that enhancing the detection performance of photodiode. Furthermore, the PIN photodiodes made of perovskite single crystal with epitaxial HBL show the sensitivities for 40 KeV, 60 KeV and 80 KeV X-ray reach 7.08 mC Gyair−1cm-2, 4.04 mC Gyair−1 cm-2 and 2.38 mC Gyair−1 cm-2 respectively.